Association of the Facial Midline with the Proportion of Incisors Measured Using the Chu’s T Probe - Vega Guerrero , Lorena (2026)
Introduction: Smile harmony depends on the alignment between the facial and dental midlines, as well as incisor proportions, both of which are key elements in orthodontic esthetics. Objectives: To analyze the relationship between the facial midline and incisor proportions. Materials and Methods: A cross-sectional observational study was conducted using 117 pretreatment models (Autonomous University of Nayarit, 2015–2025). Midline coincidence was evaluated through frontal photographs and study models, while incisor proportions were measured using Chu’s proportion gauge. Descriptive statistics and the Chi-square test were used to determine associations. Results: Coincidence between the facial and maxillary midlines was observed in 59% of cases. No statistically significant association was found between midline coincidence and the proportions of the upper (X² = 0,13, p = 0,715) or lower (X² = 0,12, p = 0,731) incisors. Conclusions: Incisor proportions are not directly related to the alignment of dental midlines with respect to the facial midline.